Osmotic Edema Rapidly Increases Neuronal Excitability Through Activation of NMDA Receptor-Dependent Slow Inward Currents in Juvenile and Adult Hippocampus. (30th September 2015) - Lauderdale, Kelli; Murphy, Thomas; Tung, Tina; Davila, David; Binder, Devin K.; Fiacco, Todd A.
Cellular edema (cell swelling) is a principal component of numerous brain disorders including ischemia, cortical spreading depression, hyponatremia, and epilepsy. Cellular edema increases seizure-like activity in vitro and in vivo, largely through nonsynaptic mechanisms attributable to reduction of the extracellular space. However, the types of excitability changes occurring in individual neurons during the acute phase of cell volume increase remain unclear. Using whole-cell patch clamp techniques, we report that one of the first effects of osmotic edema on excitability of CA1 pyramidal cells is the generation of slow inward currents (SICs), which initiate after approximately 1 min. Frequency of SICs increased as osmolarity decreased in a dose-dependent manner. Imaging of real-time volume changes in astrocytes revealed that neuronal SICs occurred while astrocytes were still in the process of swelling. SICs evoked by cell swelling were mainly nonsynaptic in origin and NMDA receptor-dependent. To better understand the relationship between SICs and changes in neuronal excitability, recordings were performed in increasingly physiological conditions. In the absence of any added pharmacological reagents or imposed voltage clamp, osmotic edema induced excitatory postsynaptic potentials and burst firing over the same timecourse as SICs. Like SICs, action potentials were blocked by NMDAR antagonists. Effects were more pronounced in adult (8–20 weeks old) compared with juvenile (P15–P21) mice. Together, our results indicate that cell swelling triggered by reduced osmolarity rapidly increases neuronal excitability through activation of NMDA receptors. Our findings have important implications for understanding nonsynaptic mechanisms of epilepsy in relation to cell swelling and reduction of the extracellular space.